(untitled) (The Pakistan Development Review, 2001)
An adequate provision of social services is a concurrent function of federal and provincial governments. However, in Pakistan, the financing and delivery of social services largely prevails in the hands of provinces and major sources of revenues in the hand of federal government, which creates vertical imbalances. Federal transfers are the mechanism for their correction and these are constituted through the National Finance Commission (NFC) Awards. The last NFC Award was constituted in 1997 and it changed both the size of divisible pool and the share of federal and provincial governments in the divisible pool. The changed provincial shares have based on higher tax revenue collection, which was not materialised during the following four-year period after the award. Therefore, provincial governments experienced the shortfall in the federal transfers during last four years after the award and have experienced a lower growth in transfers than projected in 1997 NFC Award. This is in contrast with the provincial experience during 1991 NFC Award, in which provinces had received higher revenue transfers from federal government than projected.